Tasawuf Sebagai Solusi dari Kosongnya Spiritualitas Pada Masyarakat Modern Akibat Perkembangan Teknologi - Fitrawati, Fitrawati (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This article discusses Sufism, which is a solution to the spiritual void that occurs in modern society. The purpose of this article is to explain the problem of spirituality that occurs in society due to technological developments and to explain how Sufism is a solution to the dryness of spirituality. This study aims to reintroduce the values of Sufism so that it can be applied in everyday life. Sufism values practically have benefits for human life. This study is a qualitative study based on literature data, so the thinking pattern chosen in this study is a reflective deductive-inductive pattern. By using a psychological approach. Discussing Sufism, Sufism can be defined as a science that studies the ways and ways of how a person can be as close as possible to God. while humans also have a goal in life, one of which is to get closer to God, in achieving the goal of getting closer to God, it is not enough just to carry out obligations such as praying five times a day, but also with tasawuf. Technological developments have various impacts on humans themselves, one of which is technology that makes people forget their existence and away from the life of spirituality. Spirituality is one that has an important role in building morality and directing humans to be more useful. Human spirituality will increase again by using the path of Sufism, which trains people not to put too much emphasis on lust or desire that tends to be strong for materialism